Implementasi Pendekatan Berbasis Genre dalam Pembelajaran Membaca: Studi Kasus di SMA Adiguna Bandar Lampung - Zain, M. Yanuardi; An’ars, M. Ghufroni (LPPM STKIP PGRI Bandar Lampung, 2023)
This article discusses a research conducted at Adiguna High School in Bandar Lampung regarding the implementation of Genre Based Approach in teaching reading. The study aims to investigate how Indonesian language teachers apply Genre Based Approach in teaching various types of texts and to identify the difficulties faced by the teachers in using this approach. The research method used is descriptive with observation and interview as the research instruments. Observation is conducted to obtain an overview of how Indonesian language teachers apply Genre Based Approach in teaching various types of texts, while interviews are conducted to identify the difficulties faced by the teachers in using Genre Based Approach. The results of the observation show that the teachers repeat the same activities in applying Genre Based Approach in every class, while the interview results reveal that the difficulties faced include limited student vocabulary, lack of motivation, and limited time to teach using GBA.